Discovery of hypothalamic hormones controlling pituitary function - McCann, Samuel M. (2006)
A means by which the brain could control the anterior pituitary gland was discovered by B. A. Houssay et al. (1933). In the living toad they found that portal vessels drained blood from a primary capillary plexus in the median eminence (ME) down the pituitary stalk to the sinusoids in the anterior pituitary gland. Popa and Fielding found these vessels in dead animals but believed that the blood flow was upward from the pituitary to the median eminence, a conclusion also reached in the living rabbit by G. W. Harris. Later with Green (1947), he found that the flow was downward in the living rat. Since the blood pressure in the portal vessels is very low, it is likely that, depending on the conditions, flow can be either upward or downward. Additionally, the short portal vessels carry blood from the neural lobe across the intermediate lobe to the anterior lobe, thus delivering neural lobe hormones directly in high concentrations to the anterior lobe of the gland. This fact has been largely neglected.